UK–EU Political and Economic Relations: An Exploratory Study - Riaz, Eizza; Naseem, Ayesha (Pakistan Languages and Humanities Review, 2025)
This study observes the economic and political effects of the EU and the UK. The phrase "brexit" refers to the process by which Great Britain left the European Union. Brexit is a significant political shift in the existing European political system. It affects both the UK’s and the EU’s political and economic future. Since its start, the UK has benefited from its participation in the EU. With the UK’s vote and the EU drafting an exit agreement, the UK is scheduled to depart the union on March 29, 2019. It resolved its meanings and dimensions. Since many Britons believe that Brexit is bad for the UK, there are views opposing a fresh referendum on the matter. Researchers have examined and settled the economic and political implications of "UK and EU relations" in this descriptive study. Contextualizing helps the EU play a significant role in diplomacy, improve peace and prosperity, uphold fundamental rights, and adhere to international standards. In order to support economic progress, security stability, and the freedom of human rights, the European Union also implements policies to combat hunger and preserve domestic resources.